2019
DOI: 10.3390/genes10121039
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling Identifies Candidate Genes Involved in the Salt Tolerance of the Xerophyte Pugionium cornutum

Abstract: The xerophyte Pugionium cornutum adapts to salt stress by accumulating inorganic ions (e.g., Cl − ) for osmotic adjustment and enhancing the activity of antioxidant enzymes, but the associated molecular basis remains unclear. In this study, we first found that P. cornutum could also maintain cell membrane stability due to its prominent ROS-scavenging ability and exhibits efficient carbon assimilation capacity under salt stress. Then, the candidate genes associated with the important physiological traits of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Plants use Cl – as a beneficial osmoticum by sequestering the majority into the central vacuole, and this process is currently thought to be mediated by the tonoplast-localized chloride channel CLCg ( White and Broadley, 2001 ; Teakle and Tyerman, 2010 ; Nguyen et al , 2016 ). The transcript levels of PcCLCg in the shoots of P. cornutum are highly up-regulated under treatment with 50 mM NaCl ( Cui et al , 2019 ), and hence the sequestration of Cl – into the cell vacuole to enhance OA is a vital strategy for P. cornutum plants growing under saline conditions. In saline environments, the shoot Cl – content in most crop species unavoidably accumulates to extremely high levels, and this particularly restricts the productivity of many crop species, such as soybean and perennial woody species ( Li et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants use Cl – as a beneficial osmoticum by sequestering the majority into the central vacuole, and this process is currently thought to be mediated by the tonoplast-localized chloride channel CLCg ( White and Broadley, 2001 ; Teakle and Tyerman, 2010 ; Nguyen et al , 2016 ). The transcript levels of PcCLCg in the shoots of P. cornutum are highly up-regulated under treatment with 50 mM NaCl ( Cui et al , 2019 ), and hence the sequestration of Cl – into the cell vacuole to enhance OA is a vital strategy for P. cornutum plants growing under saline conditions. In saline environments, the shoot Cl – content in most crop species unavoidably accumulates to extremely high levels, and this particularly restricts the productivity of many crop species, such as soybean and perennial woody species ( Li et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…6E , Table 2 ), suggesting that Na + and K + both also function in the OA of P. cornutum in response to NaCl. We have recently found that the expression of the tonoplast Na + /H + antiporter gene PcNHX1 , which encodes a protein mediating Na + and/or K + transport into vacuoles, is up-regulated in the shoots of P. cornutum under treatment with 50 mM NaCl ( Cui et al , 2019 ), and hence the vacuolar compartmentalization of Na + and/or K + may also be vital to its salt tolerance. The transport of Na + and K + into the vacuole is coupled with an increased influx of anionic solutes such as NO 3 – , Cl – , and malate to enhance the OA capacity and to balance the positive electrical charge in the vacuole ( Munns and Tester, 2008 ; Shabala and Shabala, 2011 ; Franco-Navarro et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the expression of transcription factors genes (TFs) changes rapidly in response to abiotic stresses [23], we analyzed differentially expressed TFs in tissues of sweet sorghum after salt treatment for 6 h. As shown in Figure 8A, 216 upregulated TFs and 72 downregulated TFs were identified in roots, and these DEGs were categorized into WRKY, MYB, NAC, bHLH, AP2/ERF, bZIP, MADS-box, HSF, ZF, GRAS families. In leaf sheaths and leaf blades, the number of differentially expressed TFs was less than in roots (Figure 8B and C).…”
Section: Identification Of Degs Encoding Transcription Factor In Root...mentioning
confidence: 99%
“…Several transcription factors (TFs) were also found to be involved in abiotic stress responses. For instance, APETALA2/Ethylene-responsive factor (e.g., RAV1 and ERF1) and zinc finger CCCH domain-containing proteins (e.g., CZF1) are induced by saline stress increasing plant tolerance and adaptation [9][10][11][12][13]. Besides TFs, other proteins encoded by stress-responsive genes, such as dehydrins (e.g., LTI30), play a pivotal role in plant defence interacting with membranes phospholipids, proteins, and DNA, thereby protecting them from damage.…”
Section: Introductionmentioning
confidence: 99%